Platelet CD36 links overweight and a prothrombotic phenotype in patients with non-valvular atrial fibrillation - Wang, Hua; Yan, Wei-hong; Gong, Lei; Song, Nian-peng; Wang, Chun-xiao; Zhong, Lin (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The pathophysiological mechanisms linking the overweight and prothrombotic state of non-valvular atrial fibrillation (NVAF) are incompletely understood. Our objective was to evaluate the effect of platelet CD36 on the risk of stroke associated with overweight in NVAF patients. Methods: A cross-sectional study enrolled 182 subjects with NVAF in two groups: normal weight (18.5< body mass index(BMI)<25.0 kg/m2) and overweight (BMI≥25.0 kg/m2). Clinical data, medical history, vital signs, transthoracic echocardiography parameters, and medication were recorded. Biochemical characteristics including blood glucose and serum lipid were analyzed in the Laboratory. Results: The expression of platelet CD36 and integrin αIIbβ3 was detected by flow cytometry. Among the 182 patients with NVAF, 68 (37.36%) were classified as normal weight, 114 (62.64%) as overweight. With an increase in BMI, waist-hip ratio, cholesterol, triglycerides, left atrium diameters, and the ratio of mitral inflow E velocity to myocardial e’ velocity in the mitral annulus (E/e’) increased significantly (P＜0.05). The mean fluorescent intensity of platelet CD36 increased significantly in overweight patients (P <0 .01), in line with platelet activation biomarkers (platelet integrin αIIbβ3). Platelet CD36 was positively correlated with BMI and platelet integrin αIIbβ3, respectively (P＜0.05). Additionally, platelet CD36 and BMI were independent risk factors for platelet activation in patients with NVAF. Conclusions: Platelet CD36 is speculated to mediate the complex crosstalk between overweight and platelet hyperactivity, leading to the prothrombotic state in overweight patients with NVAF. Platelet CD36 could be a potential target for preventing the prothrombotic state in overweight patients with NVAF.